2020
DOI: 10.1016/j.heliyon.2020.e04985
|View full text |Cite|
|
Sign up to set email alerts
|

Developing and using hints in computerized dynamic assessment of a TOEFL iBT reading exam

Abstract: This study investigated the impacts of computerized dynamic assessment (C-DA) on a TOEFL iBT reading exam among 185 upper-intermediate EFL Iranian learners. The exam included five question types: Vocabulary, detail, negative fact, purpose, and inference items whose answers yielded three types of scores: Actual, mediated, and learning potential. Results indicated statistically significant differences between actual and mediated scores with various reading ability levels in using hints in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It offers the facilitator the opportunity to instigate the development of learning processes within specific contexts and tasks, especially, when using age-appropriate and context-specific material (e.g., curriculum-based dynamic tests). The instruments designed to perform dynamic assessment can work as a complement to traditional assessments ( Hidri and Roud, 2020 ), as those tools are reactive and motivate the modifiability of the processes instead of their permanency ( Grigorenko and Sternberg, 1998 ). Fundamentally, as learners’ strengths and weaknesses can be identified, this assessment approach provides an opportunity to understand which dimensions need improvement.…”
Section: Introductionmentioning
confidence: 99%
“…It offers the facilitator the opportunity to instigate the development of learning processes within specific contexts and tasks, especially, when using age-appropriate and context-specific material (e.g., curriculum-based dynamic tests). The instruments designed to perform dynamic assessment can work as a complement to traditional assessments ( Hidri and Roud, 2020 ), as those tools are reactive and motivate the modifiability of the processes instead of their permanency ( Grigorenko and Sternberg, 1998 ). Fundamentally, as learners’ strengths and weaknesses can be identified, this assessment approach provides an opportunity to understand which dimensions need improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The last factor is learning autonomy, the statement "I need training from lecturer or expert to train-related to the structure and written expression" and 95% answered yes and 5% answered no. They need structure training and written expression, thought of lecturer and researcher have a different side where are from differences could be findings to solve and synthesizing the difficulties that come from cause and effect (Amiryousefi & Tavakoli, 2011;Hidri & Roud, 2020). While for structure and written expression collected the grammar structure understanding, read the instruction each part also could help them to understand what they have to do in that section (Fleckenstein et al, 2020;Masfufah, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays TOEFL test is one of the requirements to pass the Skripsi examination of English Education Departments at some Universities in Indonesia, it is also in Manado State University particularly in English Education Department. When the requirement of TOEFL was applied in EED, Grammar and Structure Score was the lowest score and it was a problem for the test takers (Fleckenstein et al, 2020;Hidri & Roud, 2020). Based on the results of the TOEFL from July 2017 to May 2019 in Language Proficiency Center showed that Grammar and Structure Scores were less than Listening and Reading Scores.…”
Section: Introductionmentioning
confidence: 99%